2012
DOI: 10.1136/bmjopen-2012-001538
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of the food environment on overweight and obesity in young children: a systematic review

Abstract: Background and objectiveThe increasing prevalence of childhood obesity has led to interest in its prevention, particularly through school-based and family-based interventions in the early years. Most evidence reviews, to date, have focused on individual behaviour change rather than the ‘obesogenic environment’.ObjectiveThis paper reviews the evidence on the influence of the food environment on overweight and obesity in children up to 8 years.Data sourcesElectronic databases (including MEDLINE, EMBASE, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
133
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 54 publications
3
133
0
7
Order By: Relevance
“…Heterogeneity in dietary measurement tools used and lack of homogeneity regarding SSB definition between studies were also reported. Other limitations inherent to study designs mentioned in reviews [30][31][32]35 were related to small sample sizes, short follow-ups, and convenience samples. Whether or not measurement limitations were mentioned did not influence reviews' conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneity in dietary measurement tools used and lack of homogeneity regarding SSB definition between studies were also reported. Other limitations inherent to study designs mentioned in reviews [30][31][32]35 were related to small sample sizes, short follow-ups, and convenience samples. Whether or not measurement limitations were mentioned did not influence reviews' conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Five reviews 14,18,27,28,31 did not state their source of funding, six 26,29,30,[32][33][34] were publicly funded, and two 25,35 were funded by the industry. Conflict of interest was not reported in six reviews, 18,25,28,29,31,34 authors of five reviews 26,27,30,32,35 reported not having any conflict of interest, and authors of two reviews 14,33 reported having conflict of interest (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…100 Neighborhood Food Outlets Many food outlets readily accessible to children have poor dietary choices (e.g., fast-food restaurants, convenience stores, small food stores) with high fat, large portion sizes, and sugary drink options. [111][112][113] Research shows that children who have easy access to poor quality food outlets tend to have a higher BMI and the potential to become overweight/obese when compared to children who do not have easy access to these food outlet types. 107 In addition, the built environment plays a critical role in how adolescents perceive distances and safety to these various food outlets.…”
Section: Built Environmentmentioning
confidence: 99%
“…Studies show that these types of stores, when in close proximity to neighborhoods or schools, increased the likelihood of purchases made at these food outlet types. 107,[111][112][113][114] Sanchez et al 111 indicated that minorities, specifically in neighborhoods that are predominantly Hispanic and African American, have a higher prevalence of obesity related to neighborhood food choices, and that 1/3 of all U.S. public middle and high schools have at least one fast food or convenience store within walking distance. In 2011, Leung et al 114 suggested that residents with more produce vendors or farmers markets nearby had a lower risk of being overweight/ obese.…”
Section: Built Environmentmentioning
confidence: 99%